2016
DOI: 10.1080/2162402x.2016.1226720
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic CD94/NKG2A blockade improves natural killer cell dysfunction in chronic lymphocytic leukemia

Abstract: Natural killer (NK)-cell count is predictive of chronic lymphoid leukemia (CLL) disease progression and their dysfunction is well documented, but the etiology of this is currently lacking. CLL cells have been shown to over-express HLA-E, the natural ligand for NKG2A expressed on NK-cells that generates a distinct negative signal relative to direct NK-cell cytotoxicity in other disease models. Utilizing a novel anti-NKG2A monoclonal blocking antibody (mAb), monalizumab, we explored the in vitro preclinical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 29 publications
0
102
0
Order By: Relevance
“…Although not assessed in our study, a recent report found no differences in expression of the NKG2A/CD94 inhibitory receptor on NK cells when comparing CLL patients and healthy controls, but demonstrated upregulation of its ligand, HLA-E, on CLL tumor cells as a potential NK cell evasion mechanism. 58 Our data suggest that immunotherapies that promote NK cell survival and function could improve immune responses toward CLL, especially treatments that enhance function or improve viability of the mature KIR C NK cells. NK cell boosting therapies may be especially beneficial to combat minimal residual disease after tumor-depleting therapies, or perhaps to prevent progression of indolent disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although not assessed in our study, a recent report found no differences in expression of the NKG2A/CD94 inhibitory receptor on NK cells when comparing CLL patients and healthy controls, but demonstrated upregulation of its ligand, HLA-E, on CLL tumor cells as a potential NK cell evasion mechanism. 58 Our data suggest that immunotherapies that promote NK cell survival and function could improve immune responses toward CLL, especially treatments that enhance function or improve viability of the mature KIR C NK cells. NK cell boosting therapies may be especially beneficial to combat minimal residual disease after tumor-depleting therapies, or perhaps to prevent progression of indolent disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to T cells, NK cell exhaustion has also been described in numerous cancers and chronic viral infections [47, 48]. McWilliams et al[49] showed that therapeutic blockade of CD94/NKG2A, defined as an inhibitory signaling receptor, can restore the functional activities of NK cells in CLL patients. However, expression of other co-inhibitory receptors like Tim-3 on NK cells of CLL patients had not yet been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be reversed by optimizing the clinical scheme and combination therapy [39]. Furthermore, several blocking antibodies, such as the anti-NKG2A blocking antibody monalizumab and the antiTim-3 blocking antibody MBG453 [40][41][42], target immune checkpoints on NK and T cells and can reverse NK-cell dysfunction in preclinical studies. However, the safety and efficacy of these inhibitors or combination therapies require further investigation.…”
Section: Checkpoint Inhibitormentioning
confidence: 99%